Influence of Environmental Factors on the Variability of Archaeal Communities in a Karst Wetland - Chen, Ying; Qiu, Kairui; Zhong, Ziyuan; Zhou, Tao (Frontiers in Microbiology, 2021)
Archaea are ubiquitous in many environments and play important roles, but little is known about their diversity, distribution, abundance, and impact factors in a karst environment. The present study investigated the effect of environment factors on the variability of archaea communities in the sediment of the Huixian karst wetland, the largest karst wetland in South China. Sediment core were obtained at four sampling sites with different water depth and macrophyte inhabitants, in both winter 2016 and summer 2018. Community analysis was based on PacBio sequencing and quantitative PCR of the archaeal 16S rRNA gene. The results showed that Euryarchaeota (57.4%) and Bathyarchaeota (38.7%) dominated all samples. Methanogenic Methanosarcinales (25.1%), Methanomicrobiales (13.7%), and methanotrophic archaea ANME-2d (9.0%) were the dominant Euryarchaeota, and MCG-11 (16.5%), MCG-6 (9.1%), and MCG-5b (5.5%) were the dominant Bathyarchaeota. The community composition remained stable between summer and winter, and the vertical distributions of archaeal phylum displayed two patterns among the four sampling sites. In winter samples, the archaeal 16S rRNA gene abundance was around 1.0E+10 copies per gram wet sediment and Shannon index was 7.3 ± 5, which were significantly higher than those of the summer samples and other karst environments. Correlation analysis showed that moisture content and pH were the factors that most affected the shape of the archaeal communities, the nitrate prevalence in the summer may be a key factor causing the significant decrease in archaeal abundance and diversity, and the two karst features, calcium-rich and weak alkalescent of water supplies may benefit the thriving of bathyarchaeotal subgroups MCG-11, -5b and MCG-6. These results suggest in karst wetland most of the archaea belongs to the clades with significant roles in carbon turnover, their composition remains stable, but their abundance and diversity vary significantly across seasons.